Innovative use of Sago Pith Waste in cement bricks: a sustainable approach to sand replacement - Jasni, Mohd Dzuliqyan; Seli, Hazman; Hasbullah, Shahana Adin; Mohd Yunus, Nur Syakirah; Subil, Nathanael (2025)
The increasing demand for cement bricks in large-scale construction has intensified the reliance on sand, raising environmental concerns. This study explores the incorporation of Sago Pith Waste (SPW), an agricultural by-product, as a partial replacement for sand in cement brick production to address pollution and promote sustainable waste management. Brick specimens were prepared with 0%, 3%, and 10% SPW content, maintaining a cement-sand ratio of 1:3 and a cement-water ratio of 1:2. After 28 days of curing, the bricks were tested for compressive strength, water absorption, and density. Results revealed that as the percentage of SPW increased, compressive strength and density decreased, while water absorption increased. Despite the decreased mechanical properties, all bricks-maintained water absorption levels below 20% of their dry weight, indicating acceptable structural performance. The study demonstrates that SPW can be effectively utilized in cement bricks, supporting Sustainable Development Goals (SDGs) by creating eco-friendly building materials and contributing to environmental conservation.